2021
DOI: 10.4081/aiua.2021.2.195
|View full text |Cite
|
Sign up to set email alerts
|

The new patterns of nephrolithiasis: What has been changing in the last millennium?

Abstract: Nephrolithiasis has been increasing over the last millennium. Although early epidemiologic studies have shown that kidney stones were two to three times more frequent in males than in females, recent reports have suggested that this rate is decreasing. In parallel a dramatic increase of nephrolithiasis has also been observed among children and adolescents. Furthermore, epidemiologic studies have shown a strong association between metabolic syndrome (Mets) traits and kidney stone disease. Patients with hyperten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 57 publications
0
4
0
1
Order By: Relevance
“…Nephrolithiasis is a common disease that is influenced by multiple factors. After entering the 21st century, the incidence rate of kidney stones showed a significant upward trend, and the male-to-female ratio of 3:1 narrowed 1 2. In a study of the National Health and Nutrition Examination Survey (NHANES) data from 2015 to 2018, the researchers found that the 12-month incidence of kidney stones was significantly higher than that stated in previous reports from the USA.…”
Section: Introductionmentioning
confidence: 88%
“…Nephrolithiasis is a common disease that is influenced by multiple factors. After entering the 21st century, the incidence rate of kidney stones showed a significant upward trend, and the male-to-female ratio of 3:1 narrowed 1 2. In a study of the National Health and Nutrition Examination Survey (NHANES) data from 2015 to 2018, the researchers found that the 12-month incidence of kidney stones was significantly higher than that stated in previous reports from the USA.…”
Section: Introductionmentioning
confidence: 88%
“…However, such events have also been described in non-stone formers [ 9 ], validating a multifactorial etiology hypothesis [ 10 ]. Recent studies suggest that nephrolithiasis should be regarded as a systemic disease due to the interaction of multiple risk factors [ 5 ].…”
Section: Pathophysiology and Main Molecular Mechanisms Of Nephrolithi...mentioning
confidence: 99%
“…The prevalence of kidney stone disease is generally higher in males than females [ 4 ]. However, nephrolithiasis is becoming more and more common in women than men causing a reduction of the male to female ratio [ 5 ] as proved by the increasing number of annual visits for urinary stones in women at emergency departments [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…), особенности диеты (обильное потребление животных белков и соли, гипогидратация) и др. Вместе с тем, многие патогенетические аспекты вероятности возникновения злокачественных новообразований у пациентов с МКБ в анамнезе, отражены лишь фрагментарно и требуют дальнейшего изучения [6][7][8][9].…”
unclassified